Gambaran sikap dan perilaku merokok siswa SMA/SMK terhadap bahaya rokok pasca pencantuman gambar peringatan pada kemasan rokok di wilayah kerja upt puskesmas Mengwi I Kabupaten Badung Bali 2014 - Putu Agus Sukarna (DiscoverSys Inc., 2017)
Figures higher cigarette consumption in Indonesia is a crucial national issues. Indonesia is the fourth largest cigarette consuming country in the world after China, Russia and the United States. Number of cigarettes consumed reached 260.8 billion cigarettes per year.The prevalence of smokers aged adolescents reported increased from year to year. Data up to the year 2010 indicate that there is a pattern increased prevalence of smoking in adolescence. Increased reaching up to 12.9% of adolescents, especially in the age group 15-19 years. The prevalence of smoking in adolescent males increased by 24.6% (13.7% - 38.4%) and among girls increased by 0.6% (0.3% - 0.9%).Indonesian government imposed a new policy regarding the display cigarette packs stipulated in Government Regulation No. 109 of 2012 on securing material containing addictive substances such as tobacco products for health. In the policy set back the pictures warning of the dangers of smoking on cigarette packs are expanded to an area of 40% from 15% in the form of text.Research on the picture of the attitudes and behavior of SMA / SMK in Mengwi against the dangers of smoking after the inclusion of picture warnings on cigarette packs until now still not been done. Therefore, this study aims to describe the attitudes and behavior of SMA / SMK against the dangers of cigarettes post a picture had note warning the dangers of smoking in the work area UPT Puskesmas Mengwi 1 BadungÂ